2019
DOI: 10.17576/jsm-2019-4811-15
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Characterization and Potential Health Benefit of the Hulu Langat Hot Spring in Selangor, Malaysia

Abstract: Geotourism is a means in geology that contributes to one of the 17 sustainable development goals (SDGs). One of the key areas in geology that can contribute to geotourism activities is hot spring exploration. This study, therefore explores hot springs in Hulu Langat, Selangor for their potential in geotourism based on their physico-chemical properties and their attributed health benefits potential. These renowned hot springs are Batu 16, Dusun Tua, National Youth Training Institute (IKBN), Sg. Serai, and Sg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
2
6
1
3
Order By: Relevance
“…The result of pH measurement was 6.1-6.5 (Table 1), which allows for optimal growth of thermophilic bacteria. Based on acidity or alkalinity, hot springs are generally classified into six classes, including: strong acid spring (pH < 2), acid spring (2 ≤ pH ≤ 4), weak acid spring (4 ≤ pH ≤ 6), neutral spring (6 ≤ pH ≤7.5) weak alkaline spring (7.5 ≤ pH ≤ 9) and alkaline spring (pH ≥ 9) (Simon et al 2019). This categorization is in line with the study of Ifandi and Alwi (2018), which reported on the optimum growth of thermophilic bacteria isolated from Bora Hot Springs in Central Sulawesi, at pH 6-8, indicating neutrophilic to alkalophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…The result of pH measurement was 6.1-6.5 (Table 1), which allows for optimal growth of thermophilic bacteria. Based on acidity or alkalinity, hot springs are generally classified into six classes, including: strong acid spring (pH < 2), acid spring (2 ≤ pH ≤ 4), weak acid spring (4 ≤ pH ≤ 6), neutral spring (6 ≤ pH ≤7.5) weak alkaline spring (7.5 ≤ pH ≤ 9) and alkaline spring (pH ≥ 9) (Simon et al 2019). This categorization is in line with the study of Ifandi and Alwi (2018), which reported on the optimum growth of thermophilic bacteria isolated from Bora Hot Springs in Central Sulawesi, at pH 6-8, indicating neutrophilic to alkalophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…O turismo em territórios de águas termais insere-se em um quadro mais amplo de crise ambiental, onde espalham-se pelo mundo propostas de atividades, bens e serviços classificados -ou divulgados-como "ecológicos". A crítica ao modelo turístico hegemônico gera alternativas, entre elas o turismo rural, o turismo cultural, o ecoturismo, e o também chamado turismo termal, ou geoturismo (Simon et al 2019;Drăghici et al 2016).…”
Section: Morro Itaimbéunclassified
“…Os estudos que não se restrinjam a aspectos clássicos do turismo, portanto, são demandados para que ampliem seu olhar para esta atividade enquanto componente de um contexto mais amplo, do qual fazem parte a cultura, a economia, a comunidade e sua percepção do território e as ações políticas, com foco em ações de sustentabilidade (Simon et al 2019;.…”
Section: Morro Itaimbéunclassified
See 1 more Smart Citation
“…The minerals contained in hot spring baths have been shown to cure several ailments (5). The therapeutic benefits obtained after soaking for 3-4 weeks in a hot pool include repairing and stimulating the immune system, mental and body relaxation, increasing the production of endorphins, and detoxifying toxins in the body through sweat and urine.…”
Section: Introductionmentioning
confidence: 99%